Problems of school leadership in public education schools in which women with disabilities are integrated in the Najran region from the point of view of teachers, supervisors and school leaders - AbdalNabi, Fadia Rizk Abdalgilel (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the problems of school leadership in integrated public education schools with women with disabilities in the Najran region from the point of view of teachers, supervisors and school leaders, and to reveal the differences in the degree of school leadership problems in public education schools in which women with disabilities are integrated according to the variable: , educational qualification, and teaching experience, The study used the descriptive analytical method, and this study was applied to a sample of (104) out of (104) teachers, supervisors and school leaders. The two researchers used a questionnaire about the problems of school leadership in schools of integrated public education with women with disabilities, and the results of the study revealed that the level of school leadership problems in schools of public education that are integrated with women with disabilities in the Najran region came to a medium degree with an average of (3.06) from the point of view of teachers, supervisors and school leaders. It also found that the dimension of school leadership problems related to educational aids came in the first place, followed by the problems of school leadership related to school leaders and leadership, and after problems related to the social acceptance of students with disabilities, followed by problems related to school curricula, followed by problems related to regulations and laws, followed by problems related to female teachers and supervisors of special education, and revealed the existence of statistically significant differences in the problems of school leadership in the schools of general education integrated with women with disabilities that are attributed to the variable of educational qualification and experience, in favor of the lower qualification and the least experience.
Keywords: school leadership problems; inclusion of people with disabilities; people with disabilities; public education schools; Najran region